PROFIL GANGGUAN FUNGSI KOGNITIF PENDERITA DIABETES MELITUS TIPE 2 DI RS DR M DJAMIL PADANG - Yuliarni Syafrita* (Neurona Majalah Kedokteran Neuro Sains, 2010)
INTRODUCTION OLDER AGE AND DIABETES ARE THE TWO INDEPENDENT FACTORS THAT ARE RELATED TO THE INCREASING RISK OF COGNITIVE IMPAIRMENT DIABETES PATIENT WITH COGNITIVE IMPAIRMENT MIGHT GO THROUGH DIFFICULTIES SIGNIFICANTLY IN MANAGING THEIR DISEASE